MDBT ratio as an instrument for estimation of transformation ratio organic matter of Bazhenov formation of Western Siberia (Russia); Book of Abstracts of the Communications presented to the 22nd International Meeing on Organic Geochemistry, Seville - Spain, September 12-16, 2005; Vol. 1 - Goncharov I. V. Ivan Vasilyevich; Samoilenko V. V.; Oblasov N. V.; Nosova S. V. (2005, 2005)
В фонде НТБ ТПУ отсутствует